1998
DOI: 10.1001/archopht.116.3.286
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Primary Trabeculectomy With the Use of Adjunctive Mitomycin

Abstract: To investigate the efficacy and safety of adjunctive mitomycin when used during a primary trabeculectomy within a series of 89 consecutive patients at 1 and 2 years postoperatively. Design: A cohort study of all patients who underwent primary trabeculectomy, performed by one of us (P.F.P.), between April 1, 1991, and December 31, 1994. Patients received topical mitomycin in conjunction with a corneal safety valve incision. A trabeculectomy was considered "successful" if it resulted in an intraocular pressure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(81 citation statements)
references
References 35 publications
7
70
1
1
Order By: Relevance
“…[20][21][22][23] Studies on Asian patients in South East Asia have also reported a lower success rate of trabeculectomy than the success rate reported on Caucasian populations in the western literature. 10,11,16 However, the survival of trabeculectomy improved with use of intraoperative antimetabolite as adjuvant, and the more liberal use of intraoperative antimetabolites was advocated in the Asian population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23] Studies on Asian patients in South East Asia have also reported a lower success rate of trabeculectomy than the success rate reported on Caucasian populations in the western literature. 10,11,16 However, the survival of trabeculectomy improved with use of intraoperative antimetabolite as adjuvant, and the more liberal use of intraoperative antimetabolites was advocated in the Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,16 Wong et al reported a 3-year success rate of only 36% for trabeculectomy in Asians with POAG, but the rate was higher if antimetabolite was used and approached the rate observed in Caucasians reported in the western studies. 12,[16][17][18][19][20] However, comparison of glaucoma surgical management in Asian and Caucasian populations is difficult because of the different surgical techniques, ophthalmic practice and medical care environments, and glaucoma managements in different countries.…”
Section: Introductionmentioning
confidence: 99%
“…Despite increasing use of mitomycin-C or 5-fluorouracil, several studies have reported that the rate of bleb failure is 10% -20% [11] [12]. The most common causes of bleb failure are scar formation and closure of the fistula [13].…”
Section: Introductionmentioning
confidence: 99%
“…This improves the early surgical outcome, but appears to increase the likelihood of late bleb leaks (Lamping et al, 1986;Wilensky, 1992;Chen et al, 1997;Scott et al, 1998). A number of modalities exist to treat bleb leaks (Gehring and Ciccarelli, 1972;Awan and Spaeth, 1974;Joiner et al, 1989;Pederson, 1989;Weber and Baker, 1989), including surgical procedures such as conjunctival patch grafts (Wilson and Kotas-Neumann, 1994), and scleral patch grafts in association with conjunctival advancement (Dunnington, 1950;Melamed et al, 1991;O'Connor et al, 1992;Morris et al, 1998).…”
Section: Introductionmentioning
confidence: 99%